The effect of ladder drill exercises on some physical abilities in male junior high school students - Wahyono, Muhammad; Setijono, Hari; Wiriawan, Oce; Akbar Harmono, Bayu; Nuryadi, Achmad; Pranoto, Adi; Purwoto, Septyaningrum Putri; Kholis, Moh. Nur; Zawawi, M. Anis; Puspodari, Puspodari (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to determine the effect of ladder drill 1 foot in each on the upper and lower extremities training carried out for 8 weeks on strength, speed, power, and agility. The type of the study was a quasi-experimental. Ladder drill exercises were carried out with an intensity of 80-90% HRmax, a frequency of 3x/week, for 8 weeks. Strength was measured using back and leg dynamometers, power was measured using the Force Plate/Accupower Test, speed with the 30-meter Running Speed Test, and agility with the Side Step Test. For statistical analysis, the researcher used the Statistical Package for Social Science (SPSS) version 21. The significance level was established at 0.05. The results of the analysis comparing pretest to posttest strength were as follows: strength pretest vs posttest (78.00±21.69 vs 122.10±22.16 seconds; p=0.000). For power, the comparison between pretest and posttest showed (42.40±11.92 vs 60.72±22.16 Joules; p=0.338). In terms of speed, the pretest vs posttest results were (5.13±0.24 vs 5.19±0.23 seconds; p=0.000), and for agility, the comparison between pretest and posttest revealed (15.00±4.35 vs 22.60±3.86 seconds; p=0.000). Executing ladder drill exercises at an intensity ranging from 80-90% of the maximum heart rate (HRmax), with a frequency of three times per week over an eight-week period, resulted in enhanced strength, speed, and agility among male junior high school students. Nevertheless, there was no notable impact observed in the power variable.